A capital from Münster in Thesinge (Bulletin KNOB, 2009)
Some 25 years ago, a fragment of a Romanesque foliage capital came to light in Thesinge, a few miles north-east of the city of Groningen in the northern Netherlands. It must once have decorated the Benedictine nuns’ abbey Germania. After the Reformation the chancel was adapted, albeit in a reduced shape, to serve as the Protestant church of Thesinge. This building can be dated to the middle of the thirteenth century. Thanks to excavations in 1973 and 1974 we know the general appearance of this church: it was more than forty metres long and had a transept. Foundations on the east side of the crossing are strong indications for a rood loft, which, on the basis of a somewhat vague reference in a seventeenth-century report, may even have survived until nave and transept were finally taken down in 1786. Traces in the masonry of the north wall of the chancel indicate that the conventual buildings were on this side. The rood loft thus separated the nuns’ choir form the nave and transept which served as parish church for the locals. The most logical place for our capital is somewhere in this rood loft, most likely on one of the two pilasters flanking the central passage. Though the capital is damaged, enough survives to ascertain a high quality of craftsmanship, rather unusual for this region. The stone is typical of the quarries in the Baumberge near Münster in Westphalia. Stylistically too, the capital is very close to those produced in Münster in the second quarter of the thirteenth century. Therefore it is most likely that we are dealing with a ready made imported capital here. This is a further confirmation of the importance of Westphalian sacred architecture for late Romanesque church building on both sides of the Ems estuary. The importation of sculpture from Münster is well documented for the late fifteenth and early sixteenth centuries. The Thesinge capital now strongly suggests that such importation has a much longer history.